Alterations in tryptophan metabolism and de novo NAD+ biosynthesis within the microbiota-gut-brain axis in chronic intestinal inflammation - Devereaux, Jeannie; Robinson, Ainsley M.; Stavely, Rhian; Davidson, Majid; Dargahi, Narges; Ephraim, Ramya; Kiatos, Dimitros; Apostolopoulos, Vasso; Nurgali, Kulmira (Frontiers in Medicine, 2024)
Background: Inflammatory bowel disease is an incurable and idiopathic disease characterized by recurrent gastrointestinal tract inflammation. Tryptophan metabolism in mammalian cells and some gut microbes comprise intricate chemical networks facilitated by catalytic enzymes that affect the downstream metabolic pathways of de novo nicotinamide adenine dinucleotide (NAD+) synthesis. It is hypothesized that a correlation exists between tryptophan de novo NAD+ synthesis and chronic intestinal inflammation. Methods: Transcriptome analysis was performed using high-throughput sequencing of mRNA extracted from the distal colon and brain tissue of Winnie mice with spontaneous chronic colitis and C57BL/6 littermates. Metabolites were assessed using ultra-fast liquid chromatography to determine differences in concentrations of tryptophan metabolites. To evaluate the relative abundance of gut microbial genera involved in tryptophan and nicotinamide metabolism, we performed 16S rRNA gene amplicon sequencing of fecal samples from C57BL/6 and Winnie mice. Results: Tryptophan and nicotinamide metabolism-associated gene expression was altered in distal colons and brains of Winnie mice with chronic intestinal inflammation. Changes in these metabolic pathways were reflected by increases in colon tryptophan metabolites and decreases in brain tryptophan metabolites in Winnie mice. Furthermore, dysbiosis of gut microbiota involved in tryptophan and nicotinamide metabolism was evident in fecal samples from Winnie mice. Our findings shed light on the physiological alterations in tryptophan metabolism, specifically, its diversion from the serotonergic pathway towards the kynurenine pathway and consequential effects on de novo NAD+ synthesis in chronic intestinal inflammation. Conclusion: The results of this study reveal differential expression of tryptophan and nicotinamide metabolism-associated genes in the distal colon and brain in Winnie mice with chronic intestinal inflammation. These data provide evidence supporting the role of tryptophan metabolism and de novo NAD+ synthesis in IBD pathophysiology.